Cultural Landscape Management: Aspects of Transformation in Agricultural Production Space That Shape the Deagrarisation Process and Biodiversity - Kamila MUSIAŁ (Communications of International Proceedings, 2025)
The research was carried out in 2024 in southern part of Poland, and concerned analysis of changes related to deagrarisation process, while focusing on selected transitional areas, called ecotones. These were grasslands, with estimated potential for ruminant grazing. The aim of the study was to assess some indicators and stimulants characterizing agricultural production space, in the aspect of cultural landcape management. The analysed stimulants were the average length and width of the ecotone zones, size of the fields immediately surrounding such zones, types of crops cultivated, and intensity of these crops. For the rational management of cultural landscape, there have been also considered factors such as the extent of abandonment of agricultural land use around the ecotone, and presence of not-native species, especially invasive ones. Research results show that fields of small sizes were beneficial from the point of view of the agricultural production space's condition, as they averagelly promoted the increase of the local biodiversity. In terms of the diversity of cultivated crop species, the presence of a larger number of such plant species has both environmental and cultural landscape values. For the both analysed municipalities, the transformation in agricultural production space and its impact on the biodiversity was assessed as average.
Keywords: deagrarisation; ecotones; potential for grazing; management of cultural landscape